The Fate of Mid-20th-Century Sports Loanwords from English in Polish - Dylewski, Radosław; Bator, Magdalena (Studia Anglica Posnaniensia, 2021)
In this paper we will discuss anglicisms which entered Polish over sixty years ago and remained in the sports lexicon until today. The article is a tribute to the late professor Jacek Fisiak, who offered the first in-depth analysis of sports vocabulary borrowed from English into Polish. His Ph.D. monograph (1961) and the subsequent article (1964) have shown a special place of sports terminology among anglicisms in Polish. The lexical items which Fisiak collected in the early sixties of the twentieth century have been tested not only in terms of their fate, but also the degree of grammatical and orthographic assimilation, as well as semantic changes the lexemes have undergone. The study is based on two large corpora of Polish: the Narodowy Korpus Języka Polskiego and Odkrywka, comprising texts from the 18th century until the present time.